Allosteric Communication in the Multifunctional and Redox NQO1 Protein Studied by Cavity-Making Mutations - Juan Luis Pacheco-Garcia; Dmitry S. Loginov; Ernesto Anoz-Carbonell; Pavla Vankova; Rogelio Palomino-Morales; Eduardo Salido; Petr Man; Milagros Medina; Athi N. Naganathan; Angel L. Pey (MDPI AG, 2022)
Allosterism is a common phenomenon in protein biochemistry that allows rapid regulation of protein stability; dynamics and function. However, the mechanisms by which allosterism occurs (by mutations or post-translational modifications (PTMs)) may be complex, particularly due to long-range propagation of the perturbation across protein structures. In this work, we have investigated allosteric communication in the multifunctional, cancer-related and antioxidant protein NQO1 by mutating several fully buried leucine residues (L7, L10 and L30) to smaller residues (V, A and G) at sites in the N-terminal domain. In almost all cases, mutated residues were not close to the FAD or the active site. Mutations L→G strongly compromised conformational stability and solubility, and L30A and L30V also notably decreased solubility. The mutation L10A, closer to the FAD binding site, severely decreased FAD binding affinity (≈20 fold vs. WT) through long-range and context-dependent effects. Using a combination of experimental and computational analyses, we show that most of the effects are found in the apo state of the protein, in contrast to other common polymorphisms and PTMs previously characterized in NQO1. The integrated study presented here is a first step towards a detailed structural-functional mapping of the mutational landscape of NQO1, a multifunctional and redox signaling protein of high biomedical relevance.